Flexural behavior and crack resistance of joints in hot-rolled section steel-UHPC composite deck under negative bending: Experiments and analysis - Wenyong Cai; Xudong Shao; Junhui Cao; Yang Wen; Rong Chen; Taowei Wang; Lin Peng; Lei Yu (Engineering Structures, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Interfacial engineering of core-shell Cu@Zn nanoclusters enables methane selective CO2 electroreduction via accelerated water dissociation - Wenlong Cao; Caiyu Chen; Hai Liu; Lei Yang; Tianlong Tan; Ruiyang Xu; Chengjian Ma; Tianyu Wang; Daniel Hedman; Shigeo Maruyama; Rong Xiang; Jue Wang; et al. (Chemical Engineering Journal, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Valorization of catalytically improved combustion stability for low-concentration methane in a gradient pore-density porous media burner - Yunqi Cao; Haonan Rong; Li Yang; Yifan Ding; Fang Liu; Cheng Zhai (Fuel, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Gut microbiome succession and cultivation-based functional screening during intestinal regeneration in Stichopus monotuberculatus - Xinyuan Yang; Rong Cao; Chenghao Jia; Fei Gao; Qiang Xu (Marine Environmental Research, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Effects of mineral inputs on organic phosphorus (Adenosine 5′-monophosphate) sorption and implications for its biogeochemical behavior on marine sediments - Yu Meng; Meng Lv; Xiao-Tong Zhang; Xiao-Yan Cao; Rong Chen; Gui-Peng Yang (Marine Chemistry, 2026)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Unraveling the role of pyridyl sites in UiO-67 type MOFs supported Pd NPs for boosting formic acid dehydrogenation - Jiewei Rong; Rongmei Zhang; Mai Xu; Xu Chen; Xinyue Yang; Jinsong Hu; Xiru Cao; Zhentao Liu; Chunming Xu; Chunhui Zhou; Xilong Wang (Chemical Engineering Journal, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Knockout of the Agrobacterium ILVC gene generates a valine-isoleucine auxotrophic strain for plant transformation - Yanhui Yang; Jun Lu; Tianrui Xue; Zhenli Cao; Mingjie Li; Zhongyi Zhang; Rong Wang; Tongyu Wu (Transgenic Research, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Arginyl-fructosyl-glucose and arginyl-fructose as bioactives from red ginseng: efficient aqueous preparation and their protective effects on aging-related erectile dysfunction in rats - Jialing Cao; Rong Tsao; Cheng Yang; Yun Wang; Lianfu Zhang (Food Bioscience, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Network pharmacology, molecular docking, and molecular dynamics simulation analysis reveal the molecular mechanism of halociline against gastric cancer - Xiangru Zha; Rong Ji; Yang Li; Rong Cao; Songlin Zhou (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The antibacterial activity, action mechanisms and prospects of Baicalein as an antibacterial adjuvant - Liuqing Mu; Kaiyan Xie; Rong Chen; Jiang Cao; Yang Shu; Xuebin Huang (World Journal of Microbiology and Biotechnology, 2025)

Mobile Genomic Island GEI-FN1A in Aeromonas salmonicida FN1 Contributes to the Spread of Antibiotic-Resistance Genes - Xinru Xie; Zhaorui Ren; Rong Wang; Kanglu Tian; Xindi Huang; Yang Lyu; Guangxiang Cao; Jiafang Fu (Current Microbiology, 2025)

Microplastics impair wound healing via NAT10-mediated epigenetic dysregulation of FASN-PI3K/AKT signaling - Feng-Jie Shen; Wei-Nan Cao; Xue-Chun Han; Qiu-Yue Pan; Yuan Wang; Rong Zhang; Gang Wei; Jin-Kui Yang (NanoImpact, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Insights into immune and oxidative stress in rural homemakers exposed to VOCs during typical solid fuel utilization activities - Rong Feng; Hongmei Xu; Liyan Liu; Jieting Zhou; Hongai Zhang; Zhenxing Shen; Mengyun Yang; Jian Sun; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

High-moisture soy protein extrudates with different moisture contents: Texture, structure, and in vitro digestion characteristics - Yiyu Zang; Rong Yang; Shurui Wang; Cuixia Sun; Yiguo Zhao; Yiping Cao; Wei Lu; Yin Zhang; Yapeng Fang (Food Research International, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Effects of different concentrations of N-acetylcysteine on the sperm quality, antioxidant enzyme activity, and antioxidant gene expression of cryopreserved goat semen - Xiaodong Wang; Jinhong Luo; Maosheng Cao; Yonghong Ju; Qingmeng Long; Rong Yang; Quan Ji; Guangbin Zhou; Junwei Zhang; Ruiyang Li; Xiang Chen (Theriogenology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Amadori compounds: analysis, composition in food and potential health beneficial functions - Jialing Cao; Cheng Yang; Jian Zhang; Lianfu Zhang; Rong Tsao (Critical Reviews in Food Science and Nutrition, 2025)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Effect of the spatial changes in engineering properties on municipal solid waste landfill slope stability - Rong Yang; Zengguang Xu; Junrui Chai; Cheng Cao; Jianxi Ren; Xiaoke Chang (Bulletin of Engineering Geology and the Environment, 2024)

Obtaining phenolic-rich extracts from tree nut shells biomass by room temperature green extraction: Molecular insights and attribution analysis - Ruoyu Du; Zhaobao Xiang; Xue Yang; Xinling Zhao; Qingya Cao; Rong Peng; Guizhi Zhang; Zhongyi Yin (Sustainable Chemistry and Pharmacy, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Constructing Cu9S5@CuSe heterostructures under microwave irradiation for rechargeable magnesium batteries - Mingwei Jin; Zhaoyu Xue; Heng Cao; Qianwei Zhang; Rong Jiang; Changliang Du; Lifen Yang; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Aqueous preparation of arginyl-fructosyl-glucose (a maltose-arginine AC) and determination of Amadori compounds (ACs) in red ginseng by ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) - Jialing Cao; Rong Tsao; Cheng Yang; Lianfu Zhang (Food Research International, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Short-term effects of substrate surface structure on macroinvertebrates community structure and functional characteristics - Yufu Gao; Liping Rong; Xiangyu Zhao; Xinyue Wang; Chenlu Lin; Lina Cao; Haijun Yang (Ecological Engineering, 2024)

Impacts of land use and climate change on runoff in the Shaying River Basin based on SWAT model - Jie Tao; Yang Cao; Rong Gan; Qiting Zuo; Qingli Zhao; Yinxing He (Limnology, 2024)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Current status, future prediction and offset potential of fossil fuel CO2 emissions in China - Jiaxi Cao; Jian Zhang; Ye Chen; Rong Fan; Lei Xu; Entao Wu; Yuan Xue; Junliu Yang; Yiming Chen; Bo Yang; Shuhong Wu (Journal of Cleaner Production, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

Effects of discharge angle of jet from a slot orifice on cooling performance for a perforated air ducting system in dairy cattle barn - Mengbing Cao; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2023)

Rare earth elements detoxification mechanism in the hyperaccumulator Dicranopteris linearis: [silicon-pectin] matrix fixation - Hong-Xiang Zheng; Yu-Lu Yang; Wen-Shen Liu; Ying Zhong; Yue Cao; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Martin J. Hodson; Ye-Tao Tang (Journal of Hazardous Materials, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Comparison between human olfactory sensitivity in the fasted and fed states: A systematic review and meta-analysis - Haoyu Nie; Rong Zhao; Yun Ai; Yingkai Yang; Bing Cao; Pengfei Han (Appetite, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Mutualistic microbial community of Bacillus amyloliquefaciens and recombinant Yarrowia lipolytica co-produced lipopeptides and fatty acids from food waste - Song Bai; Bin Qiao; Zheng-Jie Hou; Geng-Rong Gao; Chun-Yang Cao; Jing-Sheng Cheng; Ying-Jin Yuan (Chemosphere, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Homozygous missense mutation in CCDC155 disrupts the transmembrane distribution of CCDC155 and SUN1, resulting in non-obstructive azoospermia and premature ovarian insufficiency in humans - Huan Wu; Xin Zhang; Rong Hua; Yuqian Li; Li Cheng; Kuokuo Li; Yiyuan Liu; Yang Gao; Qunshan Shen; Guanxiong Wang; Mingrong Lv; Yuping Xu; et al. (Human Genetics, 2022)

Discrepancies in Simulated Ocean Net Surface Heat Fluxes over the North Atlantic - Chunlei Liu; Yazhu Yang; Xiaoqing Liao; Ning Cao; Jimmy Liu; Niansen Ou; Richard P. Allan; Liang Jin; Ni Chen; Rong Zheng (Advances in Atmospheric Sciences, 2022)

Heterogeneous Fenton degradation of persistent organic pollutants using natural chalcopyrite: effect of water matrix and catalytic mechanism - Jiapeng Yang; Rong Huang; Yijun Cao; Hui Wang; Andrei Ivanets; Chongqing Wang (Environmental Science and Pollution Research, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Genome-wide identification, characterisation and expression profile analysis of DEAD-box family genes in sweet potato wild ancestor Ipomoea trifida under abiotic stresses - Rong Wan; Jingran Liu; Zhengmei Yang; Panpan Zhu; Qinghe Cao; Tao Xu (Genes & Genomics, 2020)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Comparative Study on Antineoplastic Activity of Polysaccharide from Four Kinds of Sea Cucumber - Ling Zhao; Qi Liu; Xianqing Yang; Rong Cao (Journal of Ocean University of China, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

Application of Lactic Acid Bacteria (LAB) in freshness keeping of tilapia fillets as sashimi - Rong Cao; Qi Liu; Shengjun Chen; Xianqing Yang; Laihao Li (Journal of Ocean University of China, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Relationships between hemorrhage, angioarchitectural factors and collagen of arteriovenous malformations - Hongchuan Niu; Yong Cao; Xuejiang Wang; Xiaowei Xue; Lanbing Yu; Ming Yang; Rong Wang (Neuroscience Bulletin, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)